Studi Literatur: Komik Digital Sebagai Media Yang Efektif Dalam Pembelajaran Matematika - Fatmawati, Diah Ayu Fatmawati (Program Studi Pendidikan matematika STKIP PGRI Pacitan STKIP PGRI Pacitan, 2025)
This study aims to obtain information about digital comics as an effective learning medium in learning mathematics. This research uses the literature review method by collecting information related to previous research studies related to comics as effectiv e learning media in learning mathematics. This study found that digital comics are a very effective learning media to increase students' interest, motivation, learning outcomes and other activities. Digital comic learning media is one of the media preferred by students. This can be seen from the results of previous studies, which show that students respond very positively to digital comics as a learning medium.